The essence of Malay vernacular houses: towards understanding the socio-cultural and environmental values - Ghaffarian Hoseini, Amir Hosein; Dahlan, Nur Dalilah (International Society for the Study of Vernacular Settlements, 2012)
The Malay vernacular houses are inextricably intertwined with vernacular values embracing a natural harmony between architecture, people and environment. These vernacular values are comprised of socio-cultural and environmental concerns. The socio-cultural values are the spatial characteristics embodied in the functional spaces of Malay houses representing the cultural backgrounds, social requirements and actual needs of Malays. The environmental values are the spatial characteristics and locally environmental trends embodied in the functional spaces of Malay houses representing local characteristics of environment and tropic. Referring to the theoretical analysis, it is deduced that the aforementioned environmental and socio-cultural values are highly influential towards enhancing the quality of living environments inside the house leading to the enhancement of the quality of life as an expression of the degree of well-being. This study draws attention to the elaborations on the selected case models of Malay houses to scrutinize the significant vernacular values embodied in Malay houses irrespective of their type and region.